Delays in uptake of surgery for childhood cataract at a child eye health tertiary facility in sub-Saharan Africa (2019)
Background: Timely uptake of surgery is vital in the control of childhood blindness due to cataract. The aim of this study is to determine the uptake of surgery as well as the frequency and reasons for rescheduling of surgery for childhood cataract in a tertiary hospital in southwest Nigeria. Methods: A retrospective study of children with childhood cataract seen at the Paediatric Ophthalmology unit of the University College Hospital, Ibadan between 2011 and 2015. Demographic and clinical information was retrieved from case records. Caregivers of children who did not have surgery were contacted by telephone to elicit reasons why surgery was not done. Results: A total of 164 children were included in the study; 90 (54.9%) were male. The median age at presentation was 4 years with a range of 2–180 months. A total of 64 (39.0%) children had unilateral cataract. All patients were scheduled for surgery, but 123 (75%) underwent surgery. Surgery was rescheduled in 42 (34.1%) of those who had surgery. Reasons for rescheduling included financial constraints, illness, delay in paediatrician evaluation to ascertain fitness for anaesthesia and strike actions by health workers in the hospital. Conclusion: Three quarters of the children had surgery, though it had been rescheduled, at least once, in about onethird of them. Delayed uptake of surgery was mainly due to inability to afford treatment and strike actions. The need for improved coverage of health insurance especially for the paediatric age group in developing countries cannot be overemphasized. This is because good vision is an integral part of child development.